Collaborative Innovation Process in The Forest Area Management in Cijambu Village, Sumedang Regency - Shafiera Amalia; Candra Setya Nugroho (Wacana Journal of Social and Humanity Studies, 2018)
The forest area which located in Cijambu Village, Sumedang Regency is managed through collaborative innovative mechanism. To maintain the forest sustainability, the forest area is created to be ecotourism site namely Ciherang Tourism Area. By using a qualitative method, this paper aims to describe collaborative innovation process in Cijambu Village. The data which was collected by using observation, literature study and in-depth interview, indicated that there are some actors involved in Ciherang Tourism Village management, namely Perhutani, a State Owned Enterprise which has authority to organize the planning, management, concession and forest protection; LMDH, a forest village society organization, investor and village government. The roles and responsibility assigned for each actor in the Ciherang Tourism area management are adjusted by their capabilities and capacity. There is empowerment process among the actors through knowledge, information and idea sharing. This sharing process is essential in the tourism village improvement for it can generate a sense of ownership among actors involved. The collaborative innovation process is successfully achieving its goals, that is preserving the protected forest area, becoming the main tourist attraction in Sumedang Regency and also increasing the revenue for Cijambu Villagers. The success factors driving the collaborative innovation process in Cijambu Village are the high interdependence among the actors; the high level of the mutual trust; agreement on the mission; and significant gain from the innovation. Meanwhile, potential factors that inhibit collaborative innovation process are inter-organizational barrier and organizational barrier.